The Relationship Between Life Skills And The Achievements Of Jambi Porprov Athletes In 2023 - Marbun, Kaiser; Oktadinata, Alek; Yuliawan, Ely (Sekolah Tinggi Olahraga dan Kesehatan Bina Guna, 2025)
This study aims to determine the relationship between life skills and athlete achievement in athletics in the 2023 Jambi Provincial Sports Week (Porprov). Life skills in this context include aspects such as teamwork, goal setting, time management, emotional skills, interpersonal communication, social skills, leadership, and problem solving. This study is motivated by the importance of the affective aspect in supporting athlete performance, which has so far received less attention than cognitive and psychomotor aspects. The purpose of this study is to analyze the relationship between life skills, which include aspects of working time, goal setting, time management, emotional skills, interpersonal communication, social skills, leadership, and problem solving, on the achievement of athletes in athletics at the 2023 Jambi Provincial Sports Week (Porprov) and provide scientific understanding, especially life skills, in athlete achievement. This type of research uses quantitative with a correlational approach, in the form of a population questionnaire in this study were all athletic athletes who performed at the 2023 Jambi Porprov event. The sample size was 52 people, 30 of whom were male and 22 female. Based on the results of the study that has been conducted regarding the relationship between life skills and the achievements of Jambi Porprov athletes in 2023, it can be concluded that there is no significant relationship between life skills and the achievements of athletes, athletics in Jambi Porprov in 2023. Although most athletes have good life skills in aspects such as time management, interpersonal communication, and leadership, this does not directly correlate with the achievement of sports achievements. Thus, the alternative hypothesis (Ha) is rejected and the null hypothesis (H0) is accepted. However, of all the subdimensions, only emotional skills have a significance value of 0.044 (<0.05), which means that there is a significant but negative relationship between the ability to manage emotions and achievement. From the results of the study, it can be concluded that there is no significant relationship between life skills and the achievements of athletes, athletics in Jambi Porprov in 2023.